Why Are Personas the Way They Are? - Essi Häyhänen; Joni Salminen; Bernard J. Jansen (Persona Studies)
User personas are well-established in user-centered design. However, the persona creation process is not well understood. Addressing this gap, this study investigates how 29 students created personas from a realistic customer dataset. We identified six main persona creation strategies: (1) data-oriented strategy, (2) diversity strategy, (3) imaginative strategy, (4) sociability strategy, (5) self-centric strategy, and (6) mixed strategy. The most common strategy was the mixed approach seeking to create personas based on the presented data but at the same time representing demographically diverse user groups. Most commonly, the participants created four personas and they aimed at “harmony” in their creation process, e.g., by creating an even number of male and female personas. The results imply that creator-provided reasonings can increase transparency of the persona-creation process.